THE ANTIBACTERIAL COMPOUND COLLISMICIN A DERIVED FROM MARINE Streptomyces sp Q-629K - Tutik Murniasih; Kyoko Adachi (Universitas Gadjah Mada, 2008)
In our course of screening for secondary metabolite derived from marine bacterial, we isolate the antimicrobial compound collysmicin A from the ethyl acetate extract of Streptomyces sp Q-629K. Separation of this compound was carried out by silica gel open column chromatography. Purification of an active compound was done using HPLC C18 with acetonitril-water system. Determination of chemical structure was done by 1H, 13C NMR and LC-MS analysis. Collysmicin A was contained in fraction 3, fraction 7.2 and fraction 8.7. The antimicrobial assayed from purified compound Fr.8.7 gave diameter inhibition approximately 13 mm against S. aureus and 12 mm against B. subtilis.